2019
DOI: 10.1097/md.0000000000014092
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of local liposomal bupivacaine infiltration on pain and recovery after Total Joint Arthroplasty

Abstract: Background:Total Joint Arthroplasty (TJA) is gradually emerging as the treatment of choice for end-stage osteoarthritis. In the past, Perioperative liposomal bupivacaine treatment is still a controversial subject in TJA. Therefore, we write this systematic review and meta-analysis to evaluate the efficacy of liposomal bupivacaine on pain and recovery after TJA.Materials and methods:Embase, Pubmed, and Cochrane Library were comprehensively searched. Randomized controlled trials (RCTs), cohort studies were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Despite MMA protocols, which include periarticular injections, reproducible pain relief beyond the first 24 hours remains inconsistent, and a significant proportion of patients undergoing TKA still requires the use of opioids postoperatively. 1,9,25,26 In a phase 4 study (PILLAR), the use of liposomal bupivacaine 266 mg admixed with bupivacaine HCl 100 mg plus an MMA regimen resulted in a mean VAS AUC 12-48 score of 180.8 (primary end point). 20 More than 80% received >20 mg of opioid medication; the geometric mean total opioid consumption over 48 hours was 18.7 mg. 20 HTX-011, an extended-release dual-acting local anesthetic, is designed to provide analgesia for up to 72 hours and to reduce postoperative opioid consumption; it has been shown to provide superior pain relief compared with bupivacaine HCl following TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite MMA protocols, which include periarticular injections, reproducible pain relief beyond the first 24 hours remains inconsistent, and a significant proportion of patients undergoing TKA still requires the use of opioids postoperatively. 1,9,25,26 In a phase 4 study (PILLAR), the use of liposomal bupivacaine 266 mg admixed with bupivacaine HCl 100 mg plus an MMA regimen resulted in a mean VAS AUC 12-48 score of 180.8 (primary end point). 20 More than 80% received >20 mg of opioid medication; the geometric mean total opioid consumption over 48 hours was 18.7 mg. 20 HTX-011, an extended-release dual-acting local anesthetic, is designed to provide analgesia for up to 72 hours and to reduce postoperative opioid consumption; it has been shown to provide superior pain relief compared with bupivacaine HCl following TKA.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 A metaanalysis from Zhao and colleagues showed no difference in pain control and functional recovery when comparing liposomal bupivacaine and control. 21 In a randomized clinical trial, Schroer and colleagues matched liposomal bupivacaine against regular bupivacaine and found no difference in pain scores and similar narcotic use during hospitalization. 22 Studies evaluating liposomal bupivacaine have demonstrated postoperative benefits in pain relief and potential opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported lower pain scores as the benefits of extended release bupivacaine exhibited promising results [12][13][14][15][16]. However, as usage grew, results of several randomized trials, made even devoted users skeptical as the data exhibited non-superior results when compared to other modalities [7][8][9][10]. As a result, many orthopaedic surgeons have moved away from use of liposomal bupivacaine citing high cost for no presumed benefit [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, liposomal bupivacaine gained popularity due to its extended release and initial, promising results [6]. However, not long after popularity grew, a few randomized trials reported data noting non-superior results when comparing liposomal bupivacaine to other pain modalities (within an operating multi-modal pain protocol) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%